Novel polycyclic meroterpenoids with protein tyrosine phosphatase 1B inhibitory activity isolated from desert-derived fungi Talaromyces sp. HMT-8 - Xin-yi Zhai; Jin-jie Liu; Cui-duan Wang; Yi-fan Dou; Jian-hua Lv; Li-an Wang; Jin-xiu Zhang; Zhuang Li (Natural Products and Bioprospecting)
Abstract Seven previously undescribed polycyclic meroterpenoids talarines K–Q (1–7), along with five known ones (8–12), were isolated from desert-derived fungi Talaromyces sp. HMT-8. The structure of the novel compounds were elucidated using spectroscopic methods, including electronic circular dichroism (ECD), HRESIMS and nuclear magnetic resonance (NMR) spectroscopy. Among the isolated meroterpenoids, compounds 3, 5, and 7 exhibited rare chlorine substitution patterns. Halogenation, particularly chlorination, is uncommon in natural meroterpenoids and implies the involvement of halogenase enzymes during biosynthesis. Compounds 1–12 were evaluated for their inhibitory activity against protein tyrosine phosphatase 1B (PTP1B). Compounds 1–4 and 12 exhibited inhibitory activity against PTP1B with IC₅₀ values ranging from 1.74 to 17.60 μM. Among them, compounds 2 and 12 displayed significant inhibitory effects with an IC₅₀ value of 1.74 and 3.03 μM, respectively. Furthermore, Molecular docking analysis revealed that compounds 2 and 12 bind tightly to the catalytic site of PTP1B, forming key hydrogen bonding and hydrophobic interactions. Enzyme kinetics studies further demonstrated that both compounds act as competitive inhibitor. Graphical Abstract